Adaptation to High-Risk Childbearing: A Preliminary Situation-Specific Theory - Jacqueline Fawcett; Lorraine Tulman (Universidad de La Sabana, 2018)
Adaptación a la maternidad de alto riesgo: una teoría preliminar específica de la situación Adaptação à maternidade de alto risco: uma teoria preliminar específica da situação The purpose of this paper is to present a discussion of a preliminary situation-specific theory of adaptation to high-risk childbearing for expectant and new mothers and fathers. Roy's Adaptation Model guided the design and conduct of the pilot study of correlates of maternal and paternal functional status from which the theory was derived. The conceptual-theoretical-empirical structure for the study is displayed in a diagram. The concepts of the theory-functional status, physical symptoms, physical energy, psychological symptoms, and relationship quality--are identified and defined, and their linkages are identified. Implications for testing and potential use of the theory in nursing practice are discussed. To reference this article / Para citar este artículo / Para citar este artigo Fawcett J, Tulman L. Adaptation to High-Risk Childbearing: A Preliminary Situation-Specific Theory. Aquichan 2018; 18(4): 407-414. DOI: 10.5294/aqui.2018.18.4.3